Teaching second-language writing - Campbell, Cherry (Heinle & Heinle, 1998)
Part of "TeacherSource series", this title examines the issue from three distinct perspectives: Teachers' Voices, which are accounts of teacher's experiences; Frameworks, which are comprehensive discussions of theoretical issues; and Investigations, which are inquiry-based activities